A Dandelion in the Desert of the World: The Love Chase in The Bluest Eye by Toni Morrison - Hamivka, Andriana (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2023)
The Bluest Eye gives a detailed account of the ways that Afro-American girls’ and women’s lives are distorted by internalized white standards of beauty. Implicit messages that whiteness is superior are everywhere, from the white baby doll given to Claudia, the idealization of white beauty in the movies, to Pauline Breedlove’s preference for the young white girl she works for over her daughter. Adult women who have learned to hate the blackness of their bodies cannot help turning that contempt on their kids: Mrs. Breedlove believes Pecola is ugly, and Geraldine, who has lighter skin, curses Pecola’s blackness. Pecola is, indeed, the character who suffers the most from white beauty standards. For her, being beautiful is the required condition for being loved. That is why she feels that having blue eyes will make the harshness in her life disappear and be replaced by healthy affection. This hopeless desire ultimately leads to madness, which suggests that white beauty may destroy black sanity.